Enhancing the Effectiveness of Spatial Planning Processes: The Systemic Interplay of Analysis, Visualisation and Communication - Förster, Agnes; Thierstein, Alain (AESOP, 2012)
This paper investigates how the interplay of analysis, visualisation, and communication (AVC) affects the effectiveness of spatial planning processes. Motivated by growing public criticism of large-scale projects in Germany and demands for greater efficiency in urban development spending, the study hypothesises that AVC constitutes the fundamental skill set of planners. A meta-analysis of 40 international case studies (2000–2010) identifies success factors in applying AVC in real planning contexts. Findings were validated through a workshop with planning experts and semi-structured interviews with practitioners. Results confirm the relevance of AVC integration for planning practice and education, emphasising cross-disciplinary learning and the importance of making implicit professional knowledge explicit. The research highlights three next steps: deeper exploration of AVC as core elements, incorporation of temporal dynamics, and assessment of contextual factors such as governance, resources, and stakeholder concerns.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: spatial planning; planning methods; analysis; visualisation; communication; Germany; planning effectiveness